Case Report: Efficacy of Reduced Doses of Asfotase Alfa Replacement Therapy in an Infant With Hypophosphatasia Who Lacked Severe Clinical Symptoms - Fujisawa, Yasuko; Kitaoka, Taichi; Ono, Hiroyuki; Nakashima, Shinichi; Ozono, Keiichi; Ogata, Tsutomu (Frontiers in Endocrinology, 2020)
Background Hypophosphatasia is a rare bone disease characterized by impaired bone mineralization and low alkaline phosphatase activity. Here, we describe the course of bone-targeted enzyme replacement therapy with asfotase alpha for a female infant patient with hypophosphatasia who lacked apparent severe clinical symptoms. Case presentation The patient exhibited low serum alkaline phosphatase (60 U/L; age-matched reference range, 520–1,580) in a routine laboratory test at birth. Further examinations revealed skeletal demineralization and rachitic changes, as well as elevated levels of serum calcium (2.80 mmol/L; reference range, 2.25–2.75 mmol/L) and ionic phosphate (3.17 mmol/L; reference range, 1.62–2.48 mmol/L), which are typical features in patients with hypophosphatasia. Sequencing analysis of the tissue-nonspecific alkaline phosphatase (TNSALP) gene identified two pathogenic mutations: c.406C>T, p.Arg136Cys and c.979T>C, p.Phe327Leu. Thus, the patient was diagnosed with hypophosphatasia. At the age of 37 days, she began enzyme replacement therapy using asfotase alpha at the standard dose of 6 mg/kg/week. Initial therapy from the age of 37 days to the age of 58 days substantially improved rickets signs in the patient; it also provided immediate normalization of serum calcium and ionic phosphate levels. However, serum ionic phosphate returned to a high level (2.72 mmol/L), which was presumed to be a side effect of asfotase alpha. Thus, the patient’s asfotase alfa treatment was reduced to 2 mg/kg/week, which allowed her to maintain normal or near normal skeletal features thereafter, along with lowered serum ionic phosphate levels. Because the patient exhibited slight distal metaphyseal demineralization in the knee at the age of 2 years and 6 months, her asfotase alfa treatment was increased to 2.4 mg/kg/week. No signs of deterioration in bone mineralization were observed thereafter. At the age of 3 years, the patient’s motor and psychological development both appeared normal, compared with children of similar age. Conclusion This is the first report in which reduced doses of asfotase alfa were administered to an infant patient with hypophosphatasia who lacked apparent severe clinical symptoms. The results demonstrate the potential feasibility of a tailored therapeutic option based on clinical severity in patients with hypophosphatasia.